Kahan Peningkatan Struktur Jalan Rel Dalam Rangka Menambah Frekuensi Pelayanan Angkutan Kereta Api Lintas Jember-Banyuwangi - Rahayu, Siti; Sianipar, Arbi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
In order railway revitalization in Java Island and increasing of regional autonormJ are requiredresearches which could raises potential area supported by mode transport reliability.]ember is a producing regions of tobacro, coffee, resin, plate stone which located in DAOP 9 /emberand not supported road transport yet, operational performance is decreasing caused btj field constraints,